Effects of Nonylphenol on the Secretion of Catecholamines and Adrenocortical Hormones from Short-Term Incubated Rat Adrenal Glands - Kim, Hee-Su; Cheon, Yong-Pil; Lee, Sung-Ho (Balsaeng'gwa saengsig, 2023)
Previously, we showed that a chronic-low-dose nonylphenol (NP) exposure resulted in histological changes with sexually dimorphic pattern in rat adrenal glands. We hypothesized that such structural changes are closely related to the hormonal secretory patterns. To test this hypothesis, we developed the short-term adrenal incubation method, and measured the levels of catecholamines and cortical steroids using the high-performance liquid chromatography with electrochemical detection (HPLC-ECD) and specific enzyme-linked immunosorbent assay, respectively. The norepinephrine (NE) levels in media from NP-treated female adrenal, except 100 pM NP, were significantly increased [control (CTL) vs 1 nM NP, <0.001; vs 10 nM NP, <0.05; vs 100 nM NP, <0.001; vs 1 μM NP, <0.01]. The NE secretion from male adrenal was higher when treated with 100 nM and 1 μM NP (CTL vs 100 nM NP, <0.05; vs 1 μM NP, <0.05, respectively). The aldosterone level in the female adrenal media treated with 100 pM NP was significantly decreased, on the other hand, that of media treated with 10 nM NP was significantly increased (CTL vs 100 pM NP, <0.05; vs 10 nM NP, <0.01). In male adrenal media, the aldosterone levels of 10 nM, 100 nM and 1 μM NP-treated media were significantly declined (CTL vs 10 nM NP, <0.001; vs 100 nM NP, <0.001; vs 1 μM NP, <0.001). These results showed the NP treatment altered secretory pattern of aldosterone from adrenals of both sexes, showing sexual dimorphism. It may be helpful for understanding possible adrenal pathophysiology, and endocrine disrupting chemicals-related sexually dimorphic phenomena in adrenals.